2018
DOI: 10.1111/jpn.12956
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mash and crumble diets on intestinal amino acids transporters, intestinal morphology and pancreatic enzyme activity of broilers

Abstract: The objective of this study was to evaluate effects of mash and crumble pre-starter diets on pancreatic enzyme activity, intestinal morphology, gene expression of intestinal peptide and amino acid (AA) transporters of broilers. Broilers in battery cages were assigned to different feed forms of pre-starter diet from 1 to 10 days of age. Significantly increased body weight gain (BWG), feed intake (FI) and lowered FCR were observed in birds fed crumble pre-starter diet (CPD, p < 0.05). Feed forms had no effect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…To our knowledge, this study is the first published report of its kind evaluating plant extracts effects on nutrient transporters in broiler chickens under nonchallenge conditions; therefore, the mechanism of action is not clear. Previous studies have reported that the up-regulation of nutrient transporters is correlated to increased levels of circulating amino acids and improved amino acid digestibility (Osmanyan et al, 2018;Yu et al, 2017). Therefore, the observed improvement in digestive surface and amino acid digestibility (see discussions above) may have contributed to the upregulation of amino acid transporters in response to an increase in amino acid digestibility and concentration.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this study is the first published report of its kind evaluating plant extracts effects on nutrient transporters in broiler chickens under nonchallenge conditions; therefore, the mechanism of action is not clear. Previous studies have reported that the up-regulation of nutrient transporters is correlated to increased levels of circulating amino acids and improved amino acid digestibility (Osmanyan et al, 2018;Yu et al, 2017). Therefore, the observed improvement in digestive surface and amino acid digestibility (see discussions above) may have contributed to the upregulation of amino acid transporters in response to an increase in amino acid digestibility and concentration.…”
Section: Discussionmentioning
confidence: 99%
“…e increase in weight of pancreas, protease, and amylase activity significantly (P < 0.05) was described in the response to feeding crumble pre-starter diet (CPD), but the activity of lipase was not affected. Birds fed with CPD exhibited greater body weight gain (BWG) than birds fed mash pre-starter diet (MDP) at 10 days of age [167]. In contrast, the activity of pancreatic enzymes was described as decreasing the pelleting of broiler feed.…”
Section: Feed and Nutritional Managementmentioning
confidence: 99%
“…Lysine and arginine are transported in the intestinal basolateral layer by the CAT1 transporter, whose gene expression is regulated by factors, including nutrient type and density, hormones and growth factors (He et al., 2013 ; Pineda et al., 2004 ; Wang et al., 2017 ). Intestinal amino acid and peptide transporters are regulated by various factors, including genetic improvement, age, intestinal development, medicinal agents, form of feed, pathological states and nutrient density (Chen et al., 2005 ; Gilbert et al., 2008 ; He et al., 2013 ; Mahdavi et al., 2018 ; Morales et al., 2017 ; Osmanyan et al., 2018 ). Earlier studies suggest that the mRNA abundance of intestinal amino acid and peptide transporters in animals is regulated through various mechanisms, such as adaptive regulation theory (Hatzoglou et al., 2004 ), amino acid sensory pathways and amino acid‐responsive element (Fafournoux et al., 2000 ), peroxisome proliferator‐activated receptor‐α (PPARα; Shimakura et al., 2006 ), substrate supply to the intestine and intra‐enterocyte space (the 5´ upstream region of PepT1 contains substrate‐responsive elements; Chen et al., 2005 ; Mahdavi et al., 2018 ), increased mRNA stability and transcription rate (Adibi, 2003 ), plasma thyroxin (T4) levels and the state of intestinal villi (Mahdavi et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%